2007
DOI: 10.1007/s12263-007-0060-3
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of epigallocatechin-3-gallate on ischemia/reperfusion-induced injuries in the heart: STAT1 silencing flavonoid

Abstract: The beneficial effect of naturally occurring flavonoids in health is believed to be due to their strong antioxidant activity. However, recent laboratory evidence indicates the involvement of a more specific action. Here, we present evidence that, among a number of catechins present in green tea extract, only epigallocatechin-3-gallate (EGCG) exerts a strong inhibitory action on interferon-celicited activation of signal transducer and activator of transcription 1 (STAT1). Protective action of EGCG in ischemia/r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…12-14 EGCG has also been shown to suppress interferon gamma-induced phosphorylation of STAT1 at its Ser 727 and Tyr 701 residues in cancer cells and to suppress cisplatin-induced phosphorylation selectively Ser 727 in response to cisplatin in the cochlea. 4 In aspiration-induced lung tissue injury, pre-treatment with EGCG reduced levels of cytokines (TNFα and IL-1), of activated STAT1 protein, and of phosphorylated protein levels of JAK1 and JAK2, 15 which may be attributed to blockade of INF-γ induced STAT1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…12-14 EGCG has also been shown to suppress interferon gamma-induced phosphorylation of STAT1 at its Ser 727 and Tyr 701 residues in cancer cells and to suppress cisplatin-induced phosphorylation selectively Ser 727 in response to cisplatin in the cochlea. 4 In aspiration-induced lung tissue injury, pre-treatment with EGCG reduced levels of cytokines (TNFα and IL-1), of activated STAT1 protein, and of phosphorylated protein levels of JAK1 and JAK2, 15 which may be attributed to blockade of INF-γ induced STAT1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Several biochemical pathways underlying these effects have been identified (e.g. : cardio-and neurovascular protection [5,6]; neuroprotection and anti-aging [7,8]). Studies dealing with the mechanisms of the bioactivity of resveratrol, the model polyphenol used in the present work, have been summarised in recent reviews [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Epigallocatechin-3-gallate (EGCG) is an abundant polyphenol in green tea extract, which possesses antioxidant, anti-inflammatory and antitumorigenic properties, 22 , 23 , 24 , 25 , 26 and also a known inhibitor of STAT1. 21 , 27 Studies have shown beneficial effects of EGCG in treating diabetes, cancer, neurodegenerative disorders, cardiovascular disease and obesity. 28 , 29 , 30 , 31 Our interest in EGCG stems from the fact that it provides an orally effective STAT1 inhibitor with anticancer properties, which could complement the overall therapeutic benefits of cisplatin.…”
mentioning
confidence: 99%